Sister chromatid exchange in dyskeratosis congenita lymphocytes. - Burgdorf, W (1977)
Sister chromatid exchange (SCE) frequency in chromosomes from lymphocytes of a patient with dyskeratosis congenita was 12-2 per mitosis. Our 33 normal controls had a mean of 5-4 SCE per mitosis and 5 patients with Fanconi's anaemia averaged 7-6 SCE per mitosis. The rate of chromosome breakage was only 0-5% in the dyskeratosis congenita patient and 0 to 2-5% in controls, while the Fanconi's anaemia patients showed higher values.